The Congklak Game Method to Improve The Calculating Ability of Class III Students at SDN Segaralangu 01 - Anggie Al Mukhtadibillah; Febri Isnawati; Alwi Sofyan (International Journal of Science and Applied Science: Conference Series, 2020)
The background of this research is how the ability to count in the congklak game, so that students are interested in learning mathematics using the congklak game method. This study aims to describe the ability to count using the congklak game method in class III SDN Segaralangu 01. The method used in this research is the congklak game method. Data collection techniques in this study are observation techniques, interview techniques, and documentation techniques.So for this reason researchers are interested in students learning mathematics using the congklak game method. This research is on the ability to count using the congklak game method in class III SDN Segaralangu 01. This research is a qualitative descriptive study. The subject of this study was the congklak game for third-grade students at SDN Segaralangu 01 in numeracy skills. The object of this research is students of class III SDN Segaralangu 01 in the process of learning mathematics in the congklak game. The results of this study are how to learn mathematics using the congklak game method in class III at SDN Segaralangu 01. Based on the results of the research that has been done, general conclusions can be used in learning mathematics using the congklak game method.